EFFECT OF PYROLYSIS TEMPERATURE AND TIME OF LIQUID SMOKE PRODUCT FROM CANDLENUT SHELL BY PYROLYSIS PROCESS - et al., Sulhatun (International Journal of Advanced Science and Technology, 2019)
This Research conducted on a fixed batch reactor made of metal plate with a thickness of 3.0 mm. It carries 200 kegs in capacity. In this phase, the moisture of Candlenut shells might be kept in 10 - 12.5 wt. percentages. Process temperature variation in the temperature of 350 ° C, 450 ° C and 550 ° C. and variations of pyrolysis at 15, 30, 45 until 435 min. Product identification by GCMS at Optimum condition to determine the components of pyrolysis generated.